2014
DOI: 10.1002/2013gc005223
|View full text |Cite
|
Sign up to set email alerts
|

Buildup of a dynamically supported orogenic plateau: Numerical modeling of the Zagros/Central Iran case study

Abstract: The Iranian plateau is a vast inland region with a smooth average elevation of c. 1.5 km formed at the rear of the Zagros orogen as a result of the Arabia-Eurasia collision (i.e., over the last [30][31][32][33][34][35]. This collision zone is of particular interest due to its disputed resemblance to the faster Himalayan collision, which gave birth to the Tibetan plateau around 50 Myr ago. Recent studies have suggested that a recent (10-5 Ma) slab break-off event below Central Iran caused the formation of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 128 publications
(204 reference statements)
3
42
1
Order By: Relevance
“…Our definition of the plateau realm therefore differs from previous definitions, which included different sectors of the Arabia–Eurasia collision zone (e.g. Allen et al ., , ; Hatzfeld & Molnar, ; Mouthereau, ; Mouthereau et al ., ; Madanipour et al ., ; François et al ., ,b).…”
Section: Morphotectonic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Our definition of the plateau realm therefore differs from previous definitions, which included different sectors of the Arabia–Eurasia collision zone (e.g. Allen et al ., , ; Hatzfeld & Molnar, ; Mouthereau, ; Mouthereau et al ., ; Madanipour et al ., ; François et al ., ,b).…”
Section: Morphotectonic Settingmentioning
confidence: 99%
“…Regarding the long‐term evolution of the plateau, it has been suggested that the IP reached its present‐day size through shortening and thickening processes during outward propagation from the suture zone to the NE, possibly starting from ~25–22 Ma (Mouthereau, ; Mouthereau et al ., ; François et al ., ,b). The deformation fronts should have reached the UDMA, either between 17 and 10 Ma Mouthereau, ; Mouthereau et al ., ; François et al ., ,b) or during the last 10 Ma (Morley et al ., ).…”
Section: Morphotectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have suggested that elevation contrasts supported by tractions applied to the base of the lithosphere by the convecting mantle are of order a few hundred meters-the remaining <10% of the range of regional surface heights [e.g., Braun, 2010;François et al, 2014;Kaban et al, 1999Kaban et al, , 2004Le Stunff and Ricard, 1995;Solomatov, 2011, 2012;Christensen, 1994, 1999;White, 2000, 2002]. Some, however, contend that surface height variations > 1 km, and even 2 or 3 km, are maintained by stresses associated with mantle convection [e.g., Boschi et al, 2010;Flament, 2014;Flament et al, 2013Flament et al, , 2014Forte et al, 1993Forte et al, , 2010Gurnis, 1993;Husson et al, 2014;Lithgow-Bertelloni and Silver, 1998;Moucha and Forte, 2011;Moucha et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the timing of the Arabia-Eurasia continental collision is so controversial, ranging from Late Cretaceous (Berberian and King, 1981) to Miocene-Pliocene time (Guest et al, 2006b;McQuarrie et al, 2003). Recent studies indicate several lines of evidence in support of initial collision at latest Eocene to Early/Late Oligocene time (Agard et al, 2011;Allen and Armstrong, 2008;Ballato et al, 2011;Boulton and Robertson, 2007;Ershov et al, 2003;François et al, 2014;Hafkenscheid et al, 2006;Hessami et al, 2001;Homke et al, 2009Homke et al, , 2010Jolivet and Faccenna, 2000;Kargaranbafghi and Neubauer, 2015;Keskin, 2003;Morley et al, 2009;Robertson et al, 2006;Vincent et al, 2007). On the other hand, recent studies in the Turkish Plateau (e.g., Sosson et al, 2010 and references therein) propose northern and southern branches of the Neotethyan ocean with distinct subduction zones.…”
Section: Implications For Tectonic Regimementioning
confidence: 99%